Enhancing Customer Satisfaction: Exploring Hotel X'S Facilities and Service Quality in Bandung City - Diyan Putranto; Adi Sopyan; Anindita Gayatri; Barliani Dewi Setyawati; Albertus Banundoyo (Jurnal Multidisiplin Madani, 2023)
The purpose of this study is to learn how the amenities and quality of service at Hotel X in Bandung affect customer satisfaction. Sampling is done purposefully, and the Slovin formula is used to select a sample of participants. In this study, we used a Kuesioner to compile our data. The gathered data is then analyzed with a helpful linear regression technique. This was accomplished using the computer program SPSS. Research forum findings corroborate test data showing a connection between facility and service quality and consumer satisfaction. Furthermore, this study demonstrates that facilities have a significant role in influencing service quality. Subsequently, academics determined, via test f, that the combination of Hotel X's facilities and service quality had a substantial impact on customers' levels of satisfaction. This finding indicates that maintaining high-quality facilities and exceptional customer service is crucial for boosting client satisfaction in the hotel business